Rhomboid family member 2 regulates cytoskeletal stress-associated Keratin 16. - Maruthappu, T; Chikh, A; Fell, B; Delaney, P; Brooke, M; Levet, C; Moncada-Pazos, A; Ishida-Yamamoto, A; Blaydon, D; Waseem, A; Leigh, I; Freeman, M; et al. (Springer Nature, 2017)
Keratin 16 (K16) is a cytoskeletal scaffolding protein highly expressed at pressure-bearing sites of the mammalian footpad. It can be induced in hyperproliferative states such as wound healing, inflammation and cancer. Here we show that the inactive rhomboid protease RHBDF2 (iRHOM2) regulates thickening of the footpad epidermis through its interaction with K16. K16 expression is absent in the thinned footpads of irhom2(-/-) mice compared with irhom2(+/+)mice, due to reduced keratinocyte proliferation. Gain-of-function mutations in iRHOM2 underlie Tylosis with oesophageal cancer (TOC), characterized by palmoplantar thickening, upregulate K16 with robust downregulation of its type II keratin binding partner, K6. By orchestrating the remodelling and turnover of K16, and uncoupling it from K6, iRHOM2 regulates the epithelial response to physical stress. These findings contribute to our understanding of the molecular mechanisms underlying hyperproliferation of the palmoplantar epidermis in both physiological and disease states, and how this 'stress' keratin is regulated.